Leverage Ratio and its Potential For Enhancing the Effectiveness of Capital Regulation - Lukáš Pfeifer; Zdeněk Pikhart (Journal of Central Banking Theory and Practice, 2019)
The article deals with the procyclical development of risk weights and hence the risk-weighted capital ratio. The leverage ratio should be included in the regulatory reform package (CRR2) as a (non-risk-weighted) prudential backstop. The article defines the complementary relationship of capital and leverage by describing their different responses to the cyclical development associated with the change in the quality of assets in the various phases of the financial cycle. The results of the panel regression on a sample of selected countries illustrate: (i) that the banking sectors with lower capital adequacy relatively more increased the capital ratio in the period of financial stress and more often changed the structure of the assets into less risky assets for the improvement of the capital ratio, with a negative impact on profit; (ii) significantly lower pro-cyclicality of the leverage ratio than the capital ratio.
Keywords: G2; G18; G21; 330; macroprudential policy; leverage ratio; capital requirements